Performance management by co-operating and participating. Lessons learned from transfering service responsibiliy from state to municipal level - Óskar Dýrmundur Ólafsson (Icelandic Review of Politics & Administration, 2011)
Learning from decentralization of services from state to municipal level: The transfer of services from state to municipality level in the past 15 years has created an environment for learning and provides opportunities for development and innovation. This article is mainly based on findings from a case study in Akureyri, a municipality in north Iceland, which did implement services from the state to the municipal level and has been called the Akureyri model. The change was made possible by a legislative change in 1994. The case study is based on qualitative interviews with management personel about their management methods during implementation and data collection from previous sources. Findings show that cross-professional methods, wholistic solutions and a service orientated approach matter for performance. The organizational structure of the municipality support these methods and can improve performance. When managing municipalities it is recommended to put more emphasize on empowerment, learning and enable possibilities to increase efficiency by systems thinking.